Face shape processing via visual-to-auditory sensory substitution activates regions within the face processing networks in the absence of visual experience - Arbel, Roni; Heimler, Benedetta; Amedi, Amir (Frontiers in Neuroscience, 2022)
Previous evidence suggests that visual experience is crucial for the emergence and tuning of the typical neural system for face recognition. To challenge this conclusion, we trained congenitally blind adults to recognize faces via visual-to-auditory sensory-substitution (SDD). Our results showed a preference for trained faces over other SSD-conveyed visual categories in the fusiform gyrus and in other known face-responsive-regions of the deprived ventral visual stream. We also observed a parametric modulation in the same cortical regions, for face orientation (upright vs. inverted) and face novelty (trained vs. untrained). Our results strengthen the conclusion that there is a predisposition for sensory-independent and computation-specific processing in specific cortical regions that can be retained in life-long sensory deprivation, independently of previous perceptual experience. They also highlight that if the right training is provided, such cortical preference maintains its tuning to what were considered visual-specific face features.